Analisis penanaman modal dalam negeri dan penanaman modal asing dan pengaruhnya terhadap pertumbuhan ekonomi Provinsi Jambi - Hayatullah Humaini; M Safri; Etik Umiyati (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This study aims to analyze: 1) the development of domestic investment, foreign investment, and the economic growth rate of Jambi Province; 2) the influence of domestic investment and foreign investment on the economic growth of Jambi Province. The data used are secondary data from Jambi Province for the period of 2000 - 2015. Data is sourced from the Central Bureau of Statistics of Jambi Province. Data were analyzed descriptively and used multiple linear regression methods. The results of the study found that (1) the average growth of domestic investment in Jambi Province was 11.67 percent per year and foreign investment was 64.32 percent per year. During the analysis period, the average economic growth was 5.45 percent per year; (2) simultaneously and partially, domestic investment and foreign investment have a significant effect on economic growth in the economic growth of Jambi Province.